Generation and propagation of infectious prions by cyclic amplification of protein misfolding - Soto, Claudio (Henry Stewart Talks, 2008)
Prions as infectious proteins and the mechanism of replication, The rationale and proof of concept for the PMCA technology, Multiple applications of PMCA, Generation of infectious prions by PMCA, Studies of prion strains and species barrier, Use of PMCA for prion detection and diagnosis
Reviewed at 2020/05/01, Archived at 2021/02/25